Media Pembelajaran Interaktif Aksara Devanagari Sebagai Inovasi Edukasi Digital Berbasis Budaya Bali - Aristamy, I Gusti Ayu Agung Mas; Mutiarani, Rizkita Ayu; Winatha, Komang Redy; Naratama, I Made Edo (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to develop an interactive mobile application-based learning media to introduce Devanagari Sanskrit script to Indonesian teenagers. The background of this research is the lack of communicative, contextual, and engaging learning media for the digital generation in learning traditional scripts. The development method uses the ADDIE model modified with a visual communication design approach and integration of local Balinese cultural values. The results show that this media successfully combines strong visual elements, interactive voice narratives, and Balinese cultural iconography in one mobile-friendly platform. Validation from design and cultural experts shows a very high level of feasibility, supported by positive responses from student users at the Dvipantara Samskrtam Foundation. This research makes a real contribution to the preservation of traditional scripts through a digital educational approach that is adaptive to the learning needs of today's teenagers. In addition, this research also opens opportunities for the development of similar learning media for other traditional scripts, thereby increasing awareness and understanding of Indonesia's rich culture among the younger generation. By integrating technology in learning, it is hoped that the preservation of Indonesian culture can go hand in hand with the progress of the times.